Empowering the Ability of ECE Teachers to Develop an Operational Curriculum Based on Education for Sustainable Development in Tapin District. - Pratiwi, Hardiyanti; Ismail, Murniyanti; Rahmah, Sipa; Rosada, Radiana (Journal of Empowerment and Community Service (JECSR), 2023)
The curriculum is a crucial component of education. The ability to design a curriculum is an essential skill that early childhood education teachers must possess. The curriculum designed must align with the local environment and socio-cultural conditions. Education for Sustainable Development (ESD) is highly relevant to the current environmental and socio-economic context. However, the ability of early childhood education (ECE) teachers to design an ESD-based curriculum still needs to be developed. In response to this need, a mentorship program was conducted for ECE teachers in Tapin Regency using the Participatory Action Research (PAR) approach. The primary objective was to empower ECE teachers in designing an operational curriculum based on ESD in accordance with the independent curriculum concept. This activity concluded with the certification of 70 ECE teachers who participated in the mentorship program. They were equipped with the knowledge and skills to design an operational curriculum aligned with the independent and ESD-based curriculum. Each group produced teaching modules during the mentorship activities. The participants committed to implementing the teaching modules they had developed and to continuously refining them for future application. The mentorship program successfully empowered ECE teachers in Tapin Regency in designing an ESD-based operational curriculum. Further training and mentorship are still needed to enhance the skills of ECE teachers in designing more varied and engaging learning activities tailored to the characteristics of early childhood.